The Definition and Significance of Intoxication in Australian Criminal Law: A Case Study of Queensland’s Safe Night out Legislation - Quilter, J.; McNamara, L.; Seear, Kate; Room, R. (HeinOnline, 2016)
Australian criminal law is being actively reconfigured in an effort to produce a more effective response to the problem of alcohol-related violence. This article uses the Safe Night Out Legislation Amendment Act 2014 (Qld) as a case study for two purposes: i) to introduce a set of conceptual tools and typologies that can be used to investigate the relationship between ‘intoxication’ and criminal law; and ii) to raise a number of concerns about how the effects of alcohol and other drugs are implicated in laws governing police powers, criminal responsibility and punishment. We draw attention to the different and sometimes inconsistent ways in which significance is attached to evidence of the consumption of alcohol and other drugs, as well as to variations and ambiguities in how legislation attempts to capture the degree of impairment or effects that are regarded as warranting the attachment of criminal law significance.